Kolaborasi Tuberculosis (TBC) dan Human Immunodeficiency Virus (HIV) - Yona Arisena Magdalena Silitonga; Intanri Kurniati; Retno Ariza; Mukhlis Imanto; Jhond Fatriyadi S (Medula, 2019)
Tuberculosis (TBC) is becoming one of the highest causes of death in the world. Tuberculosis is caused by Mycobacterium tuberculosis that is transmitted via droplet originating from tuberculosis patients. It is estimated that one-third of people in the world have been infected by tuberculosis, but only 10-20% of people will show the symptoms. Symptoms that can arise in tuberculosis are such as bleeding cough, weight loss, night sweats, chest pain, shortness of breath and weakness. Meanwhile, human immunodeficiency virus (HIV) is a retrovirus-famili because of its ability to convert the RNA genome into DNA. HIV transmission occurs due to the entry of this virus into the body through body fluids of people who are already infected by HIV. Both of these infectious diseases alike because both of them can cause a decrease in immune system activities in the body of the sufferer. Collaboration of both diseases is common and is a deadly combination because it interacts with each other in all aspects of the disease, ranging from pathogenesis, epidemiology, clinical manifestations, treatment and prevention. Tuberculosis is also a leading cause of death in HIV-positive patients. In 2016 in Indonesia, there are found 360,565 cases of TBC, with 14% of them are also known to suffer from HIV-positive. The results of the study suggest that there is a mutual relationship between the two diseases in causing a clinical symptoms through decreased activity of the body's immune system.